Representasi Seksualitas Perempuan dalam Film Suster Keramas - Jaya, Aria Surya (Universitas Semarang, 2014)
This study aims to determine how women's sexuality in the Suster Keramas Movie represented. The author uses the theory of Baudrillard's Simulations of Jaen. Where in Jaen Simulation Baudrillard, humans inhabit a space of reality, where the difference between the real and fantasy, the original and the fake ones are very thin. Simularca is the space where reality, whether real or apparent, manipulate and simulate everything until the furthest limits. Simulacra restrictions do not have a reference, it is a duplication of a duplication, so that the difference between the original and the duplicate becomes blurred.The research method used is the method of Jaen Baudrillard simulation analysis on the basis that this study analyzed the sexuality of women who delivered in a scene in the Suster Keramas movie, which gives an explanation and overview of related formulation of the problem.Inferred outline sexuality analytical results indicate a space where all the principles of reality and truth of modernism is now challenged and even rejected. What is shown is just an exploitation of capitalism which aims to get the maximum profit.